2018
DOI: 10.1136/bmj.k3695
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention with statins for older adults

Abstract: Patient preference remains the guiding principle while we wait for better evidence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In view of the paucity of definite evidence, considering and discussing patient preference might play a relevant role …”
Section: Clues To Optimal Treatment Choicementioning
confidence: 99%
See 1 more Smart Citation
“…In view of the paucity of definite evidence, considering and discussing patient preference might play a relevant role …”
Section: Clues To Optimal Treatment Choicementioning
confidence: 99%
“…In view of the paucity of definite evidence, considering and discussing patient preference might play a relevant role. 85,94 Obviously, statin treatment in extremely frail and disabled patients, end-stage dementia patients or in the end-of-life period is not justified. 95 We need to underline that this tentative approach is largely empirical, and might benefit from direct validation.…”
Section: Assessment Of Frailtymentioning
confidence: 99%
“…Statins are widely used to lower plasma cholesterol levels. They inhibit the mevalonate pathway that mediates cholesterol synthesis ( 2 , 3 , 4 ). While use of statins effectively reduces the risk of atherosclerotic events, several studies have demonstrated that statin treatment may have adverse effects including myotoxicity, impaired insulin sensitivity and increased risk for type 2 diabetes ( 6 , 12 , 14 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…HMG-CoA reductase inhibitors, statins, lower cholesterol levels by inhibiting mevalonate formation, the rate-limiting step in the cholesterol biosynthesis ( 1 ). These drugs are widely used and effective in primary ( 2 , 3 ) and secondary ( 4 ) prevention of atherosclerotic events. However, data from several clinical studies have demonstrated that statin treatment increases the risk of type 2 diabetes ( 5 ).…”
Section: Introductionmentioning
confidence: 99%